From Ideals to Institutions: Institutional Entrepreneurship and the Growth of Mexican Small Business Finance - Canales, Rodrigo (Organization Science, 2016)
This in-depth, comparative case study of the creation of the small and medium enterprise credit market in Mexico explores the work of actors to craft new organizational practices, as well as the symbols that sustain institutionalization efforts. The study demonstrates that, to craft new institutional practices, individual actors engage in two distinct layers of institutional work. One entails purposefully visible, staged, scripted, and carefully documented work to suspend existing institutions and allow for experimentation as well as to legitimize new practices. The second entails invisible, undocumented work to recruit allies, find resources, experiment with new practices, coordinate strategies of action, and build political toolkits. While visible work—which is the focus of most research on institutional change—was determinant at every stage of the change process because of its symbolic effects, actors spent most of their time and energy on invisible work, which they referred to as “the real work.” The paper shows that every act of visible institutional work was crafted through considerable amounts of invisible institutional work. Since new practices and new symbols were crafted through gradual and iterative processes of experimentation, invisible work includes many failures that remain undocumented. It also includes the work of midlevel, invisible actors who, often, are the real and unreported agents of institutional change. The findings have implications for our understanding of the mechanisms of institutional maintenance and change.